Impacts of Antandroy Migration on Water Resources, Fisheries, and Aquatic Biodiversity - Rejo Fienena Félicité; Andrianantenaina Tsiory Eric (ite ngabdi, 2026)
Internal migration has become an important adaptation strategy to climate variability in southern Madagascar, yet its implications for natural resources remain insufficiently understood. This study investigated the impacts of Antandroy migration on water resources, fisheries, and aquatic biodiversity in the districts of Toliara I and Toliara II, Atsimo-Andrefana Region. A mixed-methods approach was employed, combining quantitative and qualitative data collected from 150 respondents through structured questionnaires, semi-structured interviews, field observations, and documentary review. Quantitative data were analyzed using descriptive statistics, while qualitative information was examined through thematic analysis. The findings reveal that migration is primarily driven by recurrent drought, food insecurity, and limited livelihood opportunities in the Androy Region. Sustained migration has increased domestic water demand, intensified fishing activities, and contributed to greater pressure on aquatic ecosystems, leading to declining water availability, reduced fishery resources, and deteriorating aquatic biodiversity. However, these environmental changes result from the combined effects of migration, climate variability, population growth, and inadequate natural resource governance rather than migration alone. This study provides an integrated understanding of the relationships between migration and aquatic resource management in southwestern Madagascar and highlights the need for coordinated policies promoting sustainable water management, responsible fisheries, biodiversity conservation, climate adaptation, and migration-sensitive development planning.